DEVELOPMENT OF MATHEMATICS TEACHING MATERIALS BASED ON SCIENTIFIC APPROACH FOR MATHEMATICS LEARNING - Heni Pujiastuti; Rudi Haryadi; Faizal Ridwan (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
This study aims to develop mathematics learning based on a scientific approach to support learning mathematics in understanding mathematical concepts. This research method is to use research and development with 4D models. The 4D model consists of four steps: determining, designing, developing, and disseminating. The subjects of this study were junior high school students with an average age of 12 years. The instrument used is the feasibility aspect of the learning media. The technique used is seen from the feasibility of teaching material media. The results showed that the visual element was 87.50%, which means that this mathematics teaching material has an excellent visualization. The part of software engineering is 94.44%, which means that mathematics teaching materials are elementary to use and access. The implementation aspect is 83.33%, which means that mathematics teaching materials can be alternative support for increasing student motivation and self-regulation. The result for content accuracy is 87.5%, which means that mathematics teaching materials have perfect content accuracy. Then for the presentation aspect is 70.83% included in both categories. The evaluation aspect is 77.78%, which means the evaluation instruments in mathematics teaching materials are varied and quite tricky. The language used is 91.67%, which means the language used in mathematics teaching materials is very communicative, easy to understand, and students' cognitive development. The teaching material is suitable for mathematics learning for junior high school students based on the results obtained.